2011
DOI: 10.1016/j.tube.2011.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Natural infection of guinea pigs exposed to patients with highly drug-resistant tuberculosis

Abstract: A natural TB infection model using guinea pigs may provide useful information for investigating differences in transmission efficiency and establishment of active disease by clinical TB strains in a highly susceptible host under controlled environmental conditions. We sought to examine the capacity of naturally transmitted multidrug-resistant M. tuberculosis to establish infection and produce active disease in guinea pigs. Guinea pigs were continuously exposed for 4 months to the exhaust air of a 6-bed multidr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 28 publications
0
76
0
Order By: Relevance
“…Testing efficacy in a natural transmission model, perhaps using guinea pigs (39), would be a more physiological test of protection. Because of limited quantities of antibody from our HCW donors, these experiments may only be possible after isolation and recombinant expression of protective mAbs from our donors.…”
Section: Discussionmentioning
confidence: 99%
“…Testing efficacy in a natural transmission model, perhaps using guinea pigs (39), would be a more physiological test of protection. Because of limited quantities of antibody from our HCW donors, these experiments may only be possible after isolation and recombinant expression of protective mAbs from our donors.…”
Section: Discussionmentioning
confidence: 99%
“…18 In a recent study conducted in Witbank, South Africa, the upper room UVGI showed approximately 86% efficacy in reducing airborne TB levels. 19 Administrative controls strengthen engineering controls and provide policy and procedural support for disease prevention in HCWs. Although 55% of the workers had been trained to use a respirator, none actually used them despite being exposed to coughing patients.…”
Section: Discussionmentioning
confidence: 99%
“…There is a renewed interest in understanding natural transmission of TB with a view to improving control measures. In the original natural transmission studies performed by Riley in the 1950s (Riley 1961), guinea pigs were used to sensitively "capture" tubercle bacilli, which were shed from patients with TB disease, and similar experimental systems are being developed (Dharmadhikari et al 2011) with funding initiatives such as the Bill and Melinda Gates Foundation, TB Vaccine Accelerator grants. The reliance on the guinea pig model has sparked several new initiatives to develop immunological reagents and assays to monitor responses to exposure/infection.…”
Section: Future Perspectives For the Model Vaccine Evaluation And Natmentioning
confidence: 99%